Eksperimen Gabungan Uji Lentur dan Implementasi Teori Wheatstone Bridge untuk Mengetahui Kekuatan Lentur dan Modulus Elastisitas Material Reng Baja Ringan - I Nyoman Ardika; I Nyoman Suardika (Prokons: Jurnal Teknik Sipil, 2021)
Abstract Lightweight steel battens are one of the elements roof frame structure buildings. The material that is widely used today is mild steel. To get optimal results use be lightweight steel battens can be done through a structural analysis. In the analysis structure of light steel battens, required the actual dimensions of the cross-section and strength the light steel battens. The actual dimensions of the cross sections are obtained by direct measurement, and strength is obtained through a laboratory testing process either tensile testing or bending testing. This research was conducted by combining the application of Wheatstone Bride theory and bending testing in determining the strength and modulus of elasticity of mild steel battens on eleven test samples of mild steel battens with a length of 600 mm each. The test result data is in the form of load relationship with voltage changes generated from the Wheatstone Bridge network on a multimeter reading connected to the Wheatstone Bridge network. The data processing of the result of the change in voltage test will produce strain, so that the load and strain relationship is obtained. Data analysis of load relationship with stretching and the load-stress relationship will describe the strain-stress relationship. From the results of data processing, the results of the research conducted were obtained yield stress (fy) 407.8739 MPa at 0.2% strain; allowable stress (fa) 271,916 MPa at 0.1333% strain; ultimate stress (fu) 616,094 MPa at a strain of 0.3021%; and Modulus of elasticity (Es) 203921 MPa. Keywords:Mild Steel, Strain, Wheatstonebridge, Stress